2005
DOI: 10.1515/iprg.2005.2.2.121
|View full text |Cite
|
Sign up to set email alerts
|

Certainty across cultures: A comparison of the degree of certainty expressed by Greek and English speaking scientific authors

Abstract: Cultural values can be important determinants of academic authors' rhetorical behavior. In particular, cultural characteristics such as uncertainty avoidance, power distance, and individualism/collectivism may a¤ect the ways authors express their certainty and commitment to their claims and appeal to group solidarity and communal opinion with a view to soliciting readers' acceptance of claims and community consensus.This paper aims to illustrate the ways such cultural characteristics differentiate the degree o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 30 publications
0
21
0
1
Order By: Relevance
“…Difficulties associated with cultural differences and different rhetorical traditions: rhetorical patterns are subject to sensible differentiation according to each scholar's cultural background, ideological baggage, and to the communities' cultural practices. This has been studied, for instance, through the perspective of intercultural pragmatics (see for instance Dahl 2004 andKoutsantoni 2005), or of contrastive rhetoric (Mauranen 2004). Such studies have shown that the rhetoric choices which do not conform to the Anglo-Saxon model have less chances to be accepted; in actual fact, different cultural backgrounds seem to give rise to deep differences, affecting not only the stylistic properties of the work but, more significantly, the authoritative credibility of the whole argumentation and, ultimately, its effective impact on the readers' community (Dudley-Evans 1997, Mauranen 2004.…”
Section: Non-anglophone Scholars and The Use Of English As The Languamentioning
confidence: 99%
“…Difficulties associated with cultural differences and different rhetorical traditions: rhetorical patterns are subject to sensible differentiation according to each scholar's cultural background, ideological baggage, and to the communities' cultural practices. This has been studied, for instance, through the perspective of intercultural pragmatics (see for instance Dahl 2004 andKoutsantoni 2005), or of contrastive rhetoric (Mauranen 2004). Such studies have shown that the rhetoric choices which do not conform to the Anglo-Saxon model have less chances to be accepted; in actual fact, different cultural backgrounds seem to give rise to deep differences, affecting not only the stylistic properties of the work but, more significantly, the authoritative credibility of the whole argumentation and, ultimately, its effective impact on the readers' community (Dudley-Evans 1997, Mauranen 2004.…”
Section: Non-anglophone Scholars and The Use Of English As The Languamentioning
confidence: 99%
“…Greek scholars have found that Greek politeness is motivated by a wish to enhance solidarity rather than the avoidance of face threats (Antonopoulou 2001;Georgakopoulou 2001; Brought to you by | University of Iowa Libraries Authenticated Download Date | 6/5/15 8:11 PM Pavlidou 1994). Linguistic behavior that is claimed to be face threatening and impolite by Brown and Levinson followers (e. g., interruptions and overlaps, abusive terms of address, imposition of opinion), has been found more often to function as solidarity building in Greek (Antonopoulou and Sifianou 2003;Koutsantoni 2004Koutsantoni , 2005aKoutsantoni , 2005bTzanne 2001). Such research suggests that theories and concepts alternative to Brown and Levinson might be more productive in explaining Greek modes of politeness.…”
Section: Background On Greek Cultural Characteristicsmentioning
confidence: 99%
“…To illustrate, a great deal of research has explored linguistic elements signalling metadiscourse functions in order to reveal tendencies in writing practices across different discourse communities (regarding language, culture and discipline) and genres (Akbari, 2017;Crawford Camiciottoli, 2010;D'Angelo, 2008;Hatipoğlu & Algı, 2017;Hu & Chao, 2015;Liu & Buckingham, 2018;Molino, 2010). Nevertheless, the research examining academic discourse in terms of such expected and accepted norms has mainly been related to what experienced scholars follow in their academic writing (for example, Koutsantoni, 2004Koutsantoni, , 2005Vassileva, 2001). In other words, there are studies which have compared the publications of experienced writers with a focus on various interpersonal relations in academic texts and this can be quite crucial for helping other members of these discourse communities to ind what is generally accepted.…”
mentioning
confidence: 99%